The Influence of Leadership Style and Work Discipline on Employee Performance at PT Karya Multi Solusi Bumi Serpong Damai Tangerang - Sam Cay; Dewi Sartika; Raden Yeti Sumiaty (JIMF (Jurnal Ilmiah Manajemen Forkamma), 2022)
The purpose of the research that the author did was to determine the effect of leadership style on employee performance, the effect of work discipline on employee performance. And to determine the effect of leadership style and work discipline together on employee performance at PT KMS Serpong. The population and sample in this study were employees at PT KMS Serpong, totaling 112 samples with a saturated sample technique. The research method used by the author is descriptive quantitative method, the method of collecting data by distributing questionnaires which is then processed using regression analysis. The test used to test the research instrument in the form of validity and reliability tests. classic assumption test, namely: normality test, multicollinearity test, and autocorrelation test. Hypothesis test consists of: correlation test, determination test Simple linear regression test, multiple linear regression test, t test (partial) and F test (simultaneous) with the help of SPSS 24 Software for Windows. Based on the results of the research on the descriptive test, it is known that the leadership style variable is the number of statements answered with agreeable words of 53.3% or with agreed criteria, work discipline variable with agreeing words of 54.7% or agreeing criteria, and those who answer agree on the variable The performance of employees who agree is 54.3% or in the category of agreeing to the statement. The results of the analysis show that there is a positive and significant influence between leadership style and work discipline on employee performance at PT KMS Serpong. This can be seen from the multiple linear regression value Y = 13,465 + 0,569 X1 + 0,447 X2, the constant value of 13.465 indicates that if the Leadership Style (X1) and Work Discipline (X2) are worth 0, then the employee performance value is 13.465. The correlation coefficient value is 0.861, the coefficient of determination of the leadership style and work discipline variables contributes an influence of 74.2%, the influence of leadership style and work discipline on employee performance is significant because it has an Fcount value of 11.065 > Ftable 3.08 and a significant value of 0.000 < 0.05.